Effect of visceral obesity on main artery elasticity and vascular age in patients with hypertension, obesity, and type 2 diabetes - M. E. Statsenko; M. V. Derevyanchenko (Российский кардиологический журнал)
Aim. To assess the effect of visceral obesity on main artery elasticity and vascular age in patients with hypertension (HTN), obesity, and type 2 diabetes (T2D).Material and methods. A total of 320 patients with stage II-III HTN aged 4570 years were divided into 4 groups: isolated HTN (group 1), HTN and obesity (group 2), HTN, obesity and T2D (group 3), HTN and T2D without obesity (group 4). We assessed the clinical status, parameters of visceral obesity, main artery elasticity, and vascular age. We used nonparametric statistics, Spearman correlation analysis.Results. At least 50% of all patients had visceral obesity, despite no BMI-estimated obesity in groups 1 and 4: 57,5 vs 100,0 vs 100,0 vs 50,0% in groups 1, 2, 3 and 4, respectively (p<0,0001).In the groups where hypertension was combined with obesity and T2D, the proportion of patients with leptin content above 32,7 ng/ml significantly increased to 80% (in total for groups 2 and 3) compared with 25,0% among HTN people without obesity (in total for groups 1 and 4). There was a significant increase in proportion of patients with a adiponectin decrease <14,6 ng/ml among patients with a combination of HTN and T2D ± obesity (45% in total for groups 3 and 4) in comparison with those with HTN and without T2D ± obesity (22,5% in total for groups 1 and 2).The visceral adiposity index (VAI) was significantly higher among patients with HTN, obesity and T2D compared with those with isolated HTN and HTN in combination with T2D only (2,96 [2,36; 3,98] vs 1,87 [1,40; 2,67] vs 2,22 [1,61; 3,26], respectively). A higher proportion of subjects with adipose tissue dysfunction was noted in groups 2 and 3 compared to groups 1 and 4 (75 vs 81,1 vs 41,5 vs 53,4%, respectively, p1-2<0,001, p1-3<0,001, p2-4=0,023, p3-4=0,002).The proportion of patients with a pulse wave velocity >10 m/s was consistently more common among patients of group 3 compared with patients in groups 1 and 2 (77,0 vs 57,9 and 55,3%, respectively, p1-3=0,004, p2-3=0,006).Vascular age was significantly lower in group 1 compared with groups 3 and 4 (64,0 [57,8; 71,0] vs 69,0 [62,0; 73,0] and 69,5 [66,0; 74,3] years, respectively), as well as in group 2 compared with group 4 (64,0 [56,5; 70,5] vs 69,5 [66,0; 74,3] years). The 5-year risk of cardiovascular events was significantly higher among patients with hypertension, obesity and T2D and those with HTN and T2D without obesity, compared with patients with isolated HTN, and with those with HTN and obesity (5,9 [3,9; 7,9] and 6,5 [4,7; 8,7] vs 4,4 [2,7; 6,8] and 3,6 [2,4; 5,8], respectively). Correlation analysis revealed the relationship between the visceral obesity parameters, main artery elasticity, vascular age and the 5-year risk of cardiovascular events, demonstrating the special aspects of HTN course in each of the studied groups.Conclusion. The paper showed peculiarities of the effect of visceral obesity on main artery elasticity and vascular age in patients with HTN in combination with obesity and T2D.